Edukasi Berbasis Komunitas: Membangun Kesadaran Orang Tua dan Remaja tentang Dampak Pernikahan Dini di Desa Ketileng Kecamatan Todanan Kabupaten Blora - Utami, Yeri; Murtyaningsih, Rina; Susilowati, Endang; Prastiawan, Muhammad Dwi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Early marriage remains a significant social issue in several parts of Indonesia, particularly in rural areas, including Ketileng Village, Todanan Subdistrict, Blora Regency. The impacts of early marriage include challenges in education, economic difficulties, reproductive health issues, and social welfare concerns. Adolescent girls are the most vulnerable group affected by these challenges. The role of STAI Muhammadiyah Blora in implementing the Tri Dharma Perguruan Tinggi (the three pillars of higher education), particularly community service, enables the institution to engage with local communities, identify, and address pressing social issues, such as early marriage. This community service program aims to raise awareness among parents and adolescents about the negative impacts of early marriage through a community-based educational approach. The activities include discussions and counseling sessions for parents and adolescents in Ketileng Village. The educational materials provided cover the health and psychological impacts of early marriage, the importance of pursuing higher education, and empowering adolescents to make better life decisions. A participatory approach is employed to encourage active community involvement in understanding and formulating solutions to the problem of early marriage. The results of this program indicate an increased understanding among parents and adolescents regarding the risks and long-term consequences of early marriage. Additionally, the program successfully facilitated the formation of discussion groups aimed at strengthening collective awareness about delaying marriage age and prioritizing education. This program is expected to be sustainable and serve as a model for other villages in efforts to reduce the prevalence of early marriage, particularly in rural areas like Blora Regency.